Different Clinical Characteristics Between Distal Cholangiocarcinoma and Pancreatic Head Carcinoma With Biliary Obstruction. Issue 10 (November 2017) - Yokoyama, Yukihiro; Ebata, Tomoki; Igami, Tsuyoshi; Sugawara, Gen; Mizuno, Takashi; Yamaguchi, Junpei; Nagino, Masato
Abstract : Objectives: The aim of this study was to compare the perioperative clinical characteristics between patients with distal cholangiocarcinoma (DCC) and pancreatic head carcinoma (PHC) with biliary obstruction. Methods: This study included patients who underwent pancreatoduodenectomy and were diagnosed with DCC (n = 85) or PHC (n = 90) by final pathological examination. Perioperative clinical characteristics were compared for patients with DCC versus PHC with biliary obstruction. Results: Median coronal thickness of the pancreatic neck was significantly greater, whereas the main pancreatic duct diameter was significantly smaller in patients with DCC than patients with PHC. Most patients with DCC (95%) had a soft pancreas, whereas only 29% of patients with PHC had. The incidence rates of overall morbidity, infectious complications, and pancreatic fistula were significantly higher in patients with DCC than those in patients with PHC. Eleven DCC patients (12%) were preoperatively misdiagnosed with PHC. Among them, intraductal ultrasonography of the bile duct was performed in 7 patients, and the presence of PHC was suspected in 3 of these patients because intraductal ultrasonography detected a small intrapancreatic mass. Conclusions: This study clearly showed different perioperative characteristics between patients with DCC and PHC. It is not uncommon to misdiagnose PHC as DCC. Intraductal ultrasonography may be helpful in differentiating DCC and PHC.